Effects of aerobic and resistance exercise for 9 months on serum free light chains in type 2 diabetes - Kim, Youyoung; Campbell, John P.; Johannsen, Neil M.; Church, Timothy S.; Cho, Eunhan; Heaney, Jennifer; Spielmann, Guillaume (Frontiers in Physiology, 2024)
Background and aims: Serum polyclonal free light chains (FLCs) levels are associated with overall survival in the general population, reflecting their utility as a biomarker of underlying immune activation and inflammation. Regular exercise is known to ameliorate low-grade inflammation in chronic diseases such as type 2 diabetes; however, the effects of different exercise training modalities on FLCs in adults with type 2 diabetes is unknown. This study investigated the effects of 9-month of aerobic, resistance or combined supervised exercise on serum FLCs in 164 patients with type 2 diabetes (age 58 ± 8 years; 63% female). Methods: 164 participants from the Health Benefits of Aerobic and Resistance Training in individuals with type 2 diabetes trial (HART-D) were randomly assigned to no exercise (n = 27), aerobic exercise alone (n = 41), resistance exercise alone (n = 49), or a combination of aerobic and resistance exercise (n = 47). Fasting serum samples were collected before and after completion of the intervention to quantify changes in kappa and lambda FLCs, and serum creatinine, using commercially-available ELISAs. Results: At baseline, combined kappa and lambda FLCs (FLC sum; calculated as kappa + lambda FLCs) were positively correlated with high-sensitive C-reactive protein (hs-CRP) (r = 0.237, p < 0.05) and fat mass (r = 0.162, p < 0.05), and negatively associated with aerobic fitness (r = −0.238, p < 0.05). While non-exercise controls exhibited an increase in FLCs over the 9-month study, exercise training blunted this increase (Δ FLC sum control arm: 3.25 ± 5.07 mg∙L-1 vs. all exercise arms: -0.252 ± 6.60 mg∙L-1, p < 0.05), regardless of exercise modality. Conclusion: Serum FLCs were associated with physical fitness and body composition in patients with type 2 diabetes. 9-month of exercise training prevented the accumulation of FLCs, regardless of exercise modality. Unlike hs-CRP—which did not change during the trial—serum FLCs may serve as a more sensitive biomarker of chronic low-grade inflammation in this population.